Country Review Report: Republic of Mozambique - African Peer Review Mechanism (African Peer Review Mechanism, 2009)
The report is divided into seven chapters. This introductory chapter is followed by Chapter Two, which provides an overview of Mozambique as a backdrop to the report. Chapters Three to Six evaluate developments and challenges in the four APRM focus areas (Democracy and Political Governance; Economic Governance and Management; Corporate Governance; and Socio-Economic Development) respectively. Each of these chapters has two sections: the first analyses the codes and standards of the APRM, while the second assesses the APRM‘s objectives for that thematic area. Each section begins with a summary of the CSAR, followed by the findings of the CRM and, finally, the APR Panel‘s recommendations on the identified challenges. Effort has also been made to highlight areas of best practice in boxes. Chapter Seven discusses the cross-cutting issues considered critical due to their wider impact on governance and thus require holistic, immediate and urgent attention. These salient issues are the following: Poverty and Inequality; Party/government/business dichotomy; Land; High levels of illiteracy; Eliminating aid dependency; Information flow and paucity of data; Inclusivity; Crime, safety and Security; Domestic violence; Capacity constraints and implementation challenge; Elections; and, Corruption. The Chapter also highlights three special issues of interest to Mozambique and the Mission - the Environment, land mines and Beira city. The NPOA received from Mozambique and the comments of the government are annexed to the report, as mandated by the APRM rules.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; economic development / desenvolvimento económico; governance / governação

Indonesia After the Asian Crisis* - Hill, Hal; Shiraishi, Takashi (Asian Economic Policy Review, 2007)
Indonesia was deeply affected by the 1997–1998 crisis, more so than its East Asian neighbors. Its economic contraction was deeper and more prolonged. It was the only one to experience a (temporary) loss of macroeconomic control. It also suffered “twin crises,” in the sense that its serious economic and financial problems were accompanied by regime collapse. Consequently, recovery was a slow and complex process, as new institutions had to be created, and old ones reformed under successive short-lived administrations. But this process is largely over. The directly elected president with a strong popular mandate is in power. The new institutional framework for economic policy-making is in place. Macroeconomic stability has been restored. Although growth has yet to return to pre-crisis levels, by 2004 per capita income and poverty incidence had recovered to levels prevailing in the mid-1990s, and in the circumstances economic recovery has arguably proceeded about as quickly as could reasonably have been expected.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; decentralization / descentralização; economic development / desenvolvimento económico

Impacto da Economia Informal na Protecção Social, Pobreza e Exclusão: A Dimensão Oculta da Informalidade em Moçambique - Francisco, António A da Silva; Paulo, Margarida (CRUZEIRO DO SUL – INSTITUTO DE INVESTIGAÇÃO PARA O DESENVOLVIMENTO JOSÉ NEGRÃO, 2006)
O trabalho anunciado no título desta monografia analisa a economia informal e a protecção social, bem como os seus impactos, directos e indirectos, no desenvolvimento económico e humano, na pobreza e na exclusão social em Moçambique. A resposta e os resultados que a monografia encontrou para as questões principais de pesquisa revelaram-se, de algum modo, surpreendentes, tanto para os promotores do estudo como para os organizadores e os próprios autores. A surpresa não é por causa da revelação que a informalidade domina a sociedade moçambicana. Afinal de contas, os números aqui reunidos, segundo os quais a economia informal domina 90% da economia de Moçambique, apenas confirmam o que as pessoas sentem e vivem na sua vida quotidiana. As surpresas reveladas neste trabalho têm a ver com os mitos e falácias em que as pesquisas sobre economia informal em Moçambique têm acreditado. Do ponto de vista analítico e prático, a presente monografia levanta um duplo desafio, um relacionado directamente com a economia informal e o outro com a protecção social.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; Social Protection PEA; economic development / desenvolvimento económico; employment / emprego; informality / informalidade; poverty / pobreza; social protection / proteção social

The Indonesian Financial Crisis: From Banking Crisis to Financial Sector Reforms, 1997-2000 - Sharma, Shalendra D. (Cornell University Press, 2001)
In mid-1998, a World Bank study grimly noted that "Indonesia is in deep economic crisis. A country that achieved decades of rapid growth, stability, and poverty reduction is now near economic collapse . . . no country in recent history, let alone one the size of Indonesia, has ever suffered such a dramatic reversal of fortune." There is bitter irony in Indonesia's fall from grace. Long hailed as a model of successful economic development, it was widely predicted to escape the fate of Thailand. Between June-August 1997, as Thailand's economy unraveled and the virulent Asian flu sent shock waves through the region, the Indonesian economy remained relatively stable—a veritable rock in the stormy sea. Even the World Bank remained upbeat about the short-term outlook, believing that a widening of the intervention band would be sufficient to ward off contagion.4 The Indonesian government, which received much praise for its swift and decisive response to the crisis, went to great lengths to assure jittery investors "that Indonesia was not Thailand." Then the unthinkable happened. Indonesia suddenly succumbed to the contagion, and, measured by the magnitude of currency depreciation and contraction of economic activity, it emerged as the most serious casualty of Asia's financial crisis. What happened? Why did Indonesia (and the other high-performing Asian economies) collapse like hollow dominoes? In the numerous post-mortems that have followed, analysts have identified a number of related factors behind the region's dramatic reversal of fortune. In the case of Indonesia, the variable that soon acquired particular salience was "crony capitalism." Initially popularized by the Economist, the term quickly took a life of its own. Soon thereafter, the distinguished MIT economist, Paul Krugman, would argue that crony capitalism lay the root of Indonesia's—and indeed, East Asia's—financial woes. Krugman describes the innerworkings and manifestations of the insidious crony capitalism in evocative prose.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; economic development / desenvolvimento económico